Nutrition knowledge attitudes and behaviour as well as perceptions of hunger and food security of caregivers in a resource limited community (Bronkhorstspruit) Gauteng Republic of South Africa - Gericke, Gerda J. (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2015.